Rosja Aleksandra Wata – Czesławowi Miłoszowi ukazana - Kaźmierczyk, Zbigniew (Acta Polono-Ruthenica, 2018)
The article displays the image of Russia through the eyes of Wat in reference to the mental Russia of Miłosz. It discusses the similarities and differences of both of the views. It indicates the affinities in experiencing the communist Russia by Avant-garde poets – futurists and poets affiliated to “Żagary” magazine. The author proves that Wat’s narration in My Century organizes the dualism of the declining West and the revolutionary East. The article’s author reveals the mistake of mixing the negative data of existence with the political reality. He indicates that this contamination resulted in Wat’s idiosyncrasy towards the Mediterranean culture and expectation for its destruction by the communist revolution. He emphasizes the dual relict nature of revolutionary eschatology. The article shows the reasons for Wat’s ideological enslavement and process of liberating from the influence of communist utopia in the reality of imprisoning Wat and exiling him deep into the empire.